Could Regulator Materialize Potential Demand for Islamic Securities? Evidence from Indonesia - Bayu Kariastanto; Aulia Ihsanin (Institute for Research and Community Empowerment (LPPM TAZKIA), 2012)
Objective – The objective of this paper is to provide a discussion whether Islamic securities enjoy larger demands than conventional securities. This paper also investigate whether regulator could effectively take a role in materializing demands for Islamic securities and whether regulator declaration is more convincing than sharia compliance declaration by another institution.Methods - We employ differences in differences (DID) regression to see the immediate, medium, and long term market response to this announcement. We also estimate cumulative abnormal returns by employing the standard market model for the robustness test.Results - We find that market reacts to sharia compliance declaration by regulator in the long-run, hence potential demands are realized and the Islamic securities will enjoy greater market power. We also provide evidence that Islamic investors are not too strict in screening Islamic securities and are willing to accept different opinions regarding sharia compliance.Conclusion - This finding could explain why Islamic finance is still growing rapidly even though there are critiques in the genuineness of sharia compliance of the current Islamic financial products/services.Keywords: Regulator, Islamic securities, sharia compliance, demand, investor confidence